From intermediate capture to functional cluster construction: Synthesis of silver clusters and their Br−/I− sensing applications - Zhixun Zhang; Juefei Dai; Cheng-Cheng Feng; Chuanhua Shi; Lebing Zhou; Xianyong Yu; Chao Yang; Xueji Zhang; Huayan Yang (Polyoxometalates, 2025)
In this study, the controlled synthesis of highly stable Ag56 clusters was achieved using 4-vinylbenzoic acid (p-VBA) and tert-butyl mercaptan as ligands by accurately tuning reaction parameters such as temperature and solvent. Additionally, intermediates Ag20, Ag31, Ag32, along with the dimers of Ag31/Ag32, Ag30-bpbenz (bpbenz: 1,4-di(4-pyridyl)benzene), and Ag31-bpe (bpe: 1,2-bis(4-pyridyl)) were successfully captured. This series of nanoclusters exhibited a distinctive fluorescence aggregation-induced redshift phenomenon owing to the π–π interactions of the ligand. Additionally, the Ag56 nanocluster serves as a near-infrared fluorescence sensor for Br− and I−, with detection limits as low as 85 and 105 nM, respectively. This study offers new insights and methodologies for the synthesis of metal clusters and their applications in ion sensing.